Monte-Carlo Determination of Dose Rates In Spherical Pressurized Water Reactor Shield - Ngoc, Le Van; Ha, Trinh Dang (Communications in Physics, 2010)
The nuclear reactor emits various kinds of nuclear radiations during operation. However, the main contributions to the radiation field in the reactor are given by neutrons and gamma rays. These radiation components are the principal concern of reactor shielding. In our study the neutron and gamma radiation dose rates at different depths in concrete bio-shield of the PWR were calculated based on spherical model for M-C simulation with using MCNP4C2. The simulation results were compared with the results obtained from calculations based on S_8P_3 spherical approximation with using the ANISN code.